E2F1‐Ror2 signaling mediates coordinated transcriptional regulation to promote G1/S phase transition in bFGF‐stimulated NIH/3T3 fibroblasts. Issue 2 (10th January 2020) - Endo, Mitsuharu; Tanaka, Yuki; Otsuka, Mako; Minami, Yasuhiro
Abstract: Ror2 signaling has been shown to regulate the cell cycle progression in normal and cancer cells. However, the molecular mechanism of the cell cycle progression upon activation of Ror2 signaling still remains unknown. Here, we found that the expression levels of Ror2 in G1‐arrested NIH/3T3 fibroblasts are low and are rapidly increased following the cell cycle progression induced by basic fibroblast growth factor (bFGF) stimulation. By expressing wild‐type or a dominant negative mutant of E2F1, we show that E2F1 mediates bFGF‐induced expression of Ror2, and that E2F1 binds to the promoter of the Ror2 gene to activate its expression. We also found that G1/S phase transition of bFGF‐stimulated NIH/3T3 cells is delayed by the suppressed expression of Ror2. RNA‐seq analysis revealed that the suppressed expression of Ror2 results in the decreased expression of various E2F target genes concomitantly with increased expression of Forkhead box O (FoxO) target genes, including p21 Cip1, and p27 Kip1 . Moreover, the inhibitory effect of Ror2 knockdown on the cell cycle progression can be restored by suppressed expression of p21 Cip1, p27 Kip1, or FoxO3a . Collectively, these findings indicate that E2F1‐Ror2 signaling mediates the transcriptional activation and inhibition of E2F1‐driven and FoxO3a‐driven cell cycle‐regulated genes, respectively, thereby promoting G1/S phase transition of bFGF‐stimulated NIH/3T3 cells.